Five new North-Eastern Iberian inscriptions on lead found in urban contexts (Castellet de Banyoles and Masies de Sant Miquel) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
This contribution presents five unpublished sheets of lead with Iberian inscriptions in north-eastern Iberian writing. Three come from Castellet de Banyoles (Tivissa), and two from Masies de Sant Miquel (Banyeres del Penedès). The first one from Tivissa is a mint proof of the kuḿ legend, the second would contain a relatively long text, but only a small longitudinal fragment survives, and the third is complete, but contains a very short text: banduleis / eiar. The first one from Banyeres contains a short and fragmented text with reading problems, while the other contains a long text of which the central spine has been preserved, in which a good number of anthroponyms are identified, such as edeśigi, tigirselgi, goroigi and tautini.
Keywords: Iberian language; Iberian script; Iberian inscription; lead sheet; Iberian city